Origem e distribuição das artérias coronárias de javalis (Sus scrofa scrofa Linnaeus, 1758) - Borges, Tânia Ribeiro Junqueira (2016)
This study aimed to verify in Sus scrofa scrofa the origin and distribution of coronary arteries. 50 wild boar hearts being from 25 males and 25 females with mean age was 08 months, are used, and obtained from commercial breeding. The coronary arteries coronary were cannulated and filled with latex 50% red colored. Afterwards, the hearts were immersed and stored in vats containing 10% formaldehyde solution for ten days. The coronary arteries and their branches were dissected until the visible ramifications. The coronary arteries the right and the left were originated in 100% of the specimens from the ascending aorta. The left coronary presented a bifurcation into paraconal interventricular branch and left circumflex branch artery in 78% samples, and presented a trifurcation into paraconal interventricular branch, left circumflex branch and medium branch in 22% samples. The right coronary artery emitted the right circumflex branch, right marginal branch (70%) and subsinuosal interventricular branch. It observed anastomoses between the paraconal branch and the subsinuosal branch and between the left circumflex branch and the right circumflex branch. It was identified left branch (100%) and the right branch (84%) to the cone. Based on the analysis of the blood supply of crux cordis, and which branch originated the interventricular subsinuosal branch, in 98% of samples it found a right coronary dominance, and a balanced circulation in 2%. The obtained results show that the coronary circulation of the wild boar is similar to the ones found in humans and swines, which may justify the usage of such animals in experimental research.